2010
DOI: 10.1186/1471-2164-11-117
|View full text |Cite
|
Sign up to set email alerts
|

General and species-specific transcriptional responses to downy mildew infection in a susceptible (Vitis vinifera) and a resistant (V. riparia) grapevine species

Abstract: BackgroundDowny mildew is a destructive grapevine disease caused by Plasmopara viticola (Berk. and Curt.) Berl. and de Toni, which can only be controlled by intensive fungicide treatments. Natural sources of resistance from wild grapevine (Vitis) species are used in conventional breeding approaches, but the signals and effectors involved in resistance in this important crop species are not well understood.ResultsEarly transcriptional changes associated with P. viticola infection in susceptible V. vinifera and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
168
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(200 citation statements)
references
References 93 publications
27
168
2
1
Order By: Relevance
“…Before the release of the grape genome sequence data by Jaillon et al (2007) and Velasco et al (2007), a few omics-based studies had been reported in grape, such as the transcriptome analyses of pathogen resistance in leaves (Fung et al, 2008;Polesani et al, 2010) and the transcriptome and proteome analyses focused on grape berry development Negri et al, 2008;LĂŒcker et al, 2009). Particularly, the accumulation of secondary metabolites is an active topic in omics-based research in grape (Ali et al, 2011).…”
Section: Omics-based Studies In Grapementioning
confidence: 99%
“…Before the release of the grape genome sequence data by Jaillon et al (2007) and Velasco et al (2007), a few omics-based studies had been reported in grape, such as the transcriptome analyses of pathogen resistance in leaves (Fung et al, 2008;Polesani et al, 2010) and the transcriptome and proteome analyses focused on grape berry development Negri et al, 2008;LĂŒcker et al, 2009). Particularly, the accumulation of secondary metabolites is an active topic in omics-based research in grape (Ali et al, 2011).…”
Section: Omics-based Studies In Grapementioning
confidence: 99%
“…Since the difference between a resistant and susceptible plant is often just a question of timing and amplitude of the adequate defence response (Polesani et al 2010), investigating a compatible interaction not only gives information on the availability of adequate defence mechanisms but will also assist in the development of new control strategies and lead to the identification of pathogen and host factors needed for disease progression. Investigating the molecular basis of plant-pathogen interactions often uncovers novel aspects of plant cell biology and signalling mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of high-throughput analysis methods and a high-quality draft of the grapevine genome sequence (1) have led to the recent application of next-generation sequencing to investigate grape berry development and pathogen infection, although few proteomic studies are available. Upon infection, plants dramatically change at the molecular and biochemical levels as reflected by global transcriptome (2)(3)(4), proteome (5,6), and metabolome (7) system analyses. These studies demonstrate the importance of the complex modulation of plant metabolism and defense responses during pathogen infection.…”
mentioning
confidence: 99%